How climate impacts the composition of wolf killed-elk in northern Yellowstone National Park ... - Wilmers, Christopher; Metz, Matthew; Stahler, Daniel; Kohl, Michel; Geremia, Chris; Smith, Douglas (Dryad, 2020)
1. While the functional response of predators is commonly measured, recent work has revealed that the age and sex composition of prey killed is often a better predictor of prey population dynamics because the reproductive value of adult females is usually higher than that of males or juveniles. 2. Climate is often an important mediating factor in determining the composition of predator kills, but we currently lack a mechanistic understanding of how the multiple facets of climate interact with prey abundance and demography to influence the composition of predator kills. 3. Over 20 winters, we monitored 17 wolf packs in Yellowstone National Park and recorded the sex, age, and nutritional condition of kills of their dominant prey – elk – in both early and late winter periods when elk are in relatively good and relatively poor condition, respectively. 4. Nutritional condition (as indicated by percent marrow fat) of wolf-killed elk varied markedly with summer plant productivity, snow water equivalent (SWE) and ...